Plenary Lecture: Knowledge Management or Knowledge-Cum-Values-Management? - Matjaž Mulej; Vojko Potočan (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
There is abundant literature on knowledge management, but we know of only two articles (of Mulej and co-authors) acknowledging interdependence of the human knowledge and the human values, recently. Mulej addressed this interdependence since his formulation of his 'Dialectical Systems Theory' in a Slovenian article in 1974 and in his best-seller book 'Creative Work and the Dialectical Systems Theory' in 1979 (in Slovenian). His co-authored English book 'Dialectical Systems Thinking and the Law of Requisite Holism concerning Innovation', Emergent Publications, Litchfield Park, Arizona (2013), contains the related novelties. The point can be simply exemplified: 'If somebody has gained knowledge on shooting with a rifle, does the person's choice to shoot whether at a paper target or at a human being depend of the person's knowledge or values?' The paper is aimed to address generation of human properties on which one's bases for action, called the subjective starting points in the Dialectical Systems Theory, and their impact over the human capacity to generate inventions and innovations in a socially responsible manner, meaning consideration of interdependence and holism in order to minimize one's detrimental impact over society, i.e. humans and nature. The addressed thesis reads: Knowledge management that fails to consider human values and other emotions is too one-sided to prevent failures, which tend to result from one's / team's lack of requisite holism; it is irrational to be only rational in human decision making and action.
Keywords: D83; 330; knowledge; knowledge-cum-values management; research; Dialectical Systems Theory; (corporate) social responsibility; new economy